Makna Gaya Penulisan Jurnalistik Berita Feature Human Interest Di Detikjabar - Bulqiyyah, Rd Marjan Siti; Kurniawan, Achmad Wildan; Yatnosaputro, Rosanti Utami Dewi Suyatman (Jurnal Pustaka Komunikasi, 2024)
The writing style in features is more flexible and can be more creative and tends to be longer than other news, the human interest feature has the ability to produce the reader’s emotional reaction. Research objectives want to know aspects of clarity of writing style such as language, narrative, sentence structure, or typical elements in writing detikjabar. The research method uses the semiotics of Charles Sanders Peirce, with a qualitative approach. Data collection techniques carried out through interviews, observation, and documentation. The results showed that the sign used by detikjabar was only a slightly transparent white watermark in the lower right corner of the picture. Objects can be a representation in mind and can be in the form of something real. The interpretant in the form of the meaning of the sign, namely January is never ashamed even though it is dressed not fashionable. In detik, certain news writing is always warning or warning in each of the first paragraphs, to remind the reader that this news contains traumatic elements. The language used is classified as formal but still maintains emotional elements of humanity in its delivery.